Anatomic variations and lesions in mandibular first molar region detected with cone beam computerized tomography - Öztekin, Faruk; Yıldırım, Tuba Talo; Ataş, Osman; Tozum, Melek Didem (Harran Üniversitesi, 2022)
Background: The aim of the present study was to evaluate the submandibular fossa (SF) depth, periodontal bone loss (PBL), furcation defects (FD) and periapical (PA) status in mandibular first molar region with cone beam computerized tomography. Materials and Methods: The retrospective study consisted of CBCT images of 402 mandibular posterior regions from 201 patients. The CBCT scans were assessed to detect the prevalence of SF depth, PBL, FD and periapical status. X2-test was used to detect whether there were significant differences in the prevalence of PBL, PA status, FD, and SF by gender and by age, by occlusion. Pearson’s coefficient was applied to evaluate the correlation between variables. Result: 90 females, 111 males, mean age of 30.52?13.08) were examined. There were significant associations between age and SF depth, PBL, FD, PA status at both right and left sides (p
Keywords: Dentistry; Diş Hekimliği